Isolation and characterization of a CO2-tolerant Lactobacillus strain from Crystal Geyser, Utah, U.S.A. - Santillan, Eugenio Felipe U.; Shanahan, Timothy M.; Omelon, Christopher R.; Major, Jonathan R.; Bennett, Philip C. (Frontiers in Earth Science, 2015)
When CO2 is sequestered into the deep subsurface, changes to the subsurface microbial community will occur. Capnophiles, microorganisms that grow in CO2-rich environments, are some organisms that may be selected for under the new environmental conditions. To determine whether capnophiles comprise an important part of CO2-rich environments, an isolate from Crystal Geyser, Utah, U.S.A., a CO2- rich spring considered a carbon sequestration analogue, was characterized. The isolate was cultured under varying CO2, pH, salinity, and temperature, as well as different carbon substrates and terminal electron acceptors (TEAs) to elucidate growth conditions and metabolic activity. Designated CG-1, the isolate is related (99%) to Lactobacillus casei in 16S rRNA gene identity, growing at PCO2 between 0 to 1.0 MPa. Growth is inhibited at 2.5 MPa, but stationary phase cultures exposed to this pressure survive beyond 5 days. At 5.0 MPa, survival is at least 24 hours. CG-1 grows in neutral pH, 0.25 M NaCl, and between 25° to 45°C andconsumes glucose, lactose, sucrose, or crude oil, likely performing lactic acid fermentation. Fatty acid profiles between 0.1 MPa to 1.0 MPa suggests decreases in cell size and increases in membrane rigidity. Transmission electron microscopy reveals rod shaped bacteria at 0.1 MPa. At 1.0 MPa, cells are smaller, amorphous, and produce abundant capsular material. Its ability to grow in environments regardless of the presence of CO2 suggests we have isolated an organism that is more capnotolerant than capnophilic. Results also show that microorganisms are capable of surviving the stressful conditions created by the introduction of CO2 for sequestration. Furthermore, our ability to culture an environmental isolate indicates that organisms found in CO2 environments from previous genomic and metagenomics studies are viable, metabolizing, and potentially affecting the surrounding environment.